A Few of Our Favorite Things
VIII, 136 p.
Keywords: We are all familiar with the expression “teachers’ bag of tricks.” It is fairly easy for K-12 teachers to do a quick web search, scan library shelves, and browse through journals to provide them with numerous lessons and ideas to keep their bags filled. Science teacher educators need to not only provide preservice teachers with resources to help them fill their “bags,” but also include crucial theory and pedagogy; what constitutes “minds on” lessons, not merely “hands on” activities. But where do we science methods instructors find ideas to put in our “bag of tricks” to help us with the pedagogy we teach and model? These kinds of teaching ideas are not so easy to find using the internet or even science methods textbooks. This book is a collection of some favorite teaching ideas from science teacher educators from across the United States and abroad. This book is NOT a collection of teaching ideas about specific science content. This book IS a set of activities that help us prepare our preservice science teachers in the areas of: Constructivism/Conceptual Change; Nature of Science; Integration (including Technology Integration), Scientific Inquiry/Engineering Design; and Diversity/Differentiation. Each section starts with a brief overview of the topic and an introduction to the activities included on the theme. The individual activities include step-by-step instructions, modifications/extensions, references, and additional readings to help you easily and fully implement the idea in your own classroom. These ideas are a few of our favorites; we hope they will become some of yours as well.